The relationship between workplace conflict and job performance among the employees in Sarawak Energy Berhad/ Siti Aisyah Suhaili… [et al.] - Suhaili, Siti Aisyah; Amir Zadah, Zaifeeda Zada; Robinson, Jasmine Sinja; Robin, Michelle (2019)
This chapter will discuss the study of the relationship between workplace conflict and employee’s job performance. This chapter explains the background of the study, statement of the problem, research objective, research questions, significant of the study, limitation of the study, and definition of the terms.